Age-dependent role of steroids in the regulation of growth of the hen follicular wall - Lebedev Vladimir A; Lebedeva Irina Y; Grossmann Roland; Parvizi Nahid (BMC, 2010)
Abstract Background The ovaries are the primary targets of senescence effects in mammalian and avian species. In the present study, relationships between reproductive aging, sex steroids and the growth pattern of the pre-ovulatory follicle wall were investigated using young hens with long clutch (YLC), old hens with long clutch (OLC), old hens with short clutch (OSC), and old hens with interrupted long clutch (OILC). Methods Experiment 1: Hens were sacrificed 1.5 and 14.5 h after ovulation. Experiment 2: YLC and OILC hens were sacrificed 3.5 h after treatments with LH and/or aminoglutethimide (AG), an inhibitor of steroid synthesis. Volumes of pre-ovulatory follicles (F1-F5) and plasma concentrations of ovarian steroids were determined. Experiment 3: Granulosa and theca cells from F3 follicles of OSC and/or YLC hens were exposed in vitro to estradiol-17beta (E2), testosterone (T) and LH and the proliferative activity of the cells was examined using CellTiter 96 Aqueous One Solution Assay. Results In YLC and OLC groups, the total volume of F1-F5 follicles rose between 1.5 and 14.5 h after ovulation (P < 0.01), negatively correlating with the plasma level of E2 (P < 0.01). There was no growth of pre-ovulatory follicles in the middle of the ovulatory cycle in the OSC group, with a positive correlation being present between E2 and the follicular volume (P < 0.05). In young hens, AG caused a rise in the total follicular volume. This rise was associated with a fall in E2 (r = -0.54, P < 0.05). E2 enhanced proliferation of granulosa cells from YLC and OSC groups. The proliferative activity of granulosa and theca cells of YLC hens depended on the interaction between T and LH (P < 0.01). Conclusions These data indicate for the first time that the growth pattern of pre-ovulatory follicles during the ovulatory cycle changes in the course of reproductive aging. E2 seems to play a dual role in this adjustment; it stimulates the growth of the follicular wall in reproductive aged hens, whereas it may inhibit this process in young birds. T and LH are apparently involved in the growth regulation during the pre-ovulatory surge in young hens.